Short Communication: Aplocheilus panchax Hamilton, 1822 Found at Acidic Waters of Abandoned Ex-tin Mining Ponds as Insectivorous Fish and Its Role for Water Quality Improvement - Diah Mustikasari; Andri Kurniawan (Jurnal Ilmu Lingkungan, 2024)
Kepala timah fish or blue panchax is one of the species found at acidic waters of abandoned ex-tin mining pond. Kepala timah fish belongs to the extremophile fishes which can survive in extreme aquatic environments caused by pressure from environmental factors. This study aimed to confirm the kepala timah fish as a species of Aplocheilus panchax and to analyze its natural food habits. Molecular analysis through DNA barcoding was carried out by analyzing the COI gene and confirming the sequence of kepala timah fish in the gene bank on the NCBI website and constructing a phylogenetic tree for kepala timah fish to other A. panchax populations. Analysis of food habits was carried out by identifying the contents of the digestive tract of kepala timah fish which were observed microscopically. The results showed that kepala timah fish found at acidic waters of abandoned ex-tin mining pond was confirmed as Aplocheilus panchax Hamilton, 1822. Some morphological characters confirmed the similarity between kepala timah fish and A. panchax such as a silvery white spot on its head, terminal type of the mouth position, body shape was sagittiform, small dorsal fin on posterior body, and the shape of the caudal fin was rounded or rhomboid. Analysis of the contents of digestive tract showed the food habits of A. panchax found at acidic waters of ex-tin mining pond was insects. The food habits explained that A. panchax was classified as larvivorous or insectivorous fishes. The presence of A. panchax and its metabolic activity at abandoned ex-tin mining ponds can contributed to increasing organic matter in the waters so that it can be beneficial for improving water quality.